Ramos de Azevedo através das páginas do Correio Paulistano - Melo, Daniela Lino (2021)
Ramos de Azevedo was the most important name of architecture in São Paulo during the First Republic. He and his office were responsible for giving new features to the Republican city. This research aims to investigate how Ramos de Azevedo is projected by the newspaper Correio Paulistano, through the analysis of the news published between 1868 and 1930, tracing a route, through the evidences gathered in the pages of this periodic of how this actor became a figure of such value in the reconstruction of the Republican City of São Paulo, not only thinking of him as an architect, but as a teacher, businessman, politician, intellectual and philanthropist